2023
DOI: 10.1155/2023/9955409
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Problem-Based Learning in College of Medicine: An Indicator of Quality Education in a Hybrid Curriculum

Abstract: Background. A culture of quality is believed to drive institutes toward excellence through feedback. Multiple surveys at educational institute help to get a deeper insight into institutional performance and curricular execution. Since problem-based learning (PBL) is an important component of the hybrid curriculum, thus stakeholders’ opinion on PBL satisfaction is worth discussing. This study intended to determine the trends in students’ satisfaction with PBL over the years and to report on the importance of cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…Also, the superiority of the experimental group, who studied using the P 5 BL model, over the control group with regard to deep understanding can be explained due to model giving learners a conceptual understanding of biological concepts through active learning, dialogue, discussion, and practicing scientific activities and various thinking processes, such as understanding, application, analysis, synthesis and evaluation, building scientific explanations, and the exploration of new knowledge structures and their application in the context of real -world problems (Abed et al, 2023;Almulhem & Almulhem, 2022;Fruchter, 2000;Fruchter & Lewis, 2003).…”
Section: Groupmentioning
confidence: 99%
“…Also, the superiority of the experimental group, who studied using the P 5 BL model, over the control group with regard to deep understanding can be explained due to model giving learners a conceptual understanding of biological concepts through active learning, dialogue, discussion, and practicing scientific activities and various thinking processes, such as understanding, application, analysis, synthesis and evaluation, building scientific explanations, and the exploration of new knowledge structures and their application in the context of real -world problems (Abed et al, 2023;Almulhem & Almulhem, 2022;Fruchter, 2000;Fruchter & Lewis, 2003).…”
Section: Groupmentioning
confidence: 99%
“…Whether it is general-purpose or subject-specific, they all focus on the classroom environment, teaching support, curriculum content, teacher-student interaction, and other dimensions (Wang Yuan, 2020). To drive a research institution towards excellence, it is necessary to feed back the execution through the evaluation of the teaching quality of the curriculums (Seraj, S.A., 2023). Żyluk, A., et al (2020) investigated the curriculum, quality, and Completion assessment feedback and concluded that students had high expectations only for the four-year university surgery curriculum and the results of that curriculum, which may have implications for revisions to the curriculum and methods of teaching undergraduates in surgery.…”
Section: Objectivesmentioning
confidence: 99%
“…Problem Based Learning (PBL) is learning that uses problems as a context for students to learn about critical thinking, problem solving skills, gaining important knowledge and concepts from subject matter (Susilawati & Supriyatno, 2023). According to Abed et al (2023) PBL is a process where students are given a problem or trigger in the form of a video, image, statement, or case, and allow them to work together to solve it. So the aim of this research is to determine the level of validity of the physics e-module based on problem based learning as independent teaching material to improve the critical thinking skills of class XI high school students.…”
Section: Introductionmentioning
confidence: 99%